IMPROVING STUDENTS’ SPEAKING SKILL THROUGH CHAIN STORY TECHNIQUE - Rahmawati Ramadani; Yohanes Gatot Sutapa Yuliana; Luwandi Suhartono (Universitas Tanjungpura, 2022)
The aim of this study is to improve the students’ pronunciation and fluency using chain story technique to the second grade students of SMP Negeri 1 Sukadana in academic year 2019/2020. In this research, the researcher used chain story as technique to solve the students’ problems. The method of this research was a classroom action research, it was done in two cycles. The subject of the research was twenty eight students of the second grade in class VIII E. The findings showed that during teaching and learning process, the students were more confident in speaking and enthusiastic following the activity in the classroom. The chain story technique could also improve students’ speaking skill in front of class. This could be seen from the improvement of students’ fluency and pronunciations, the students could pronounce the vocabulary correctly. In addition, the students also improved their abilities to speak fluently after being taught by chain story technique. It can be concluded that the use of chain story technique improved the students’ fluency and pronunciation.